Peran Psikologi Pendidikan dalam Pembelajaran di Sekolah Dasar - Regina Sipayung; Patri Janson Silaban; Nove Riski Manik; Gabrielli Ambarita; Siska Ginting; Boyan Sinaga; Rudolf Simamora (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Educational psychology plays an important role in the context of learning in primary schools. Educational psychology helps teachers understand the basics of educational psychology, learning theories in psychology, and various learning methods that can be used. Educational psychology also contributes to the development of educational curriculum, student character building, and evaluation of learning outcomes.One of the relevant learning theories is cybernetic learning theory. This theory considers learning as information processing, where the information system processed and learned by students becomes more important than the learning process itself. In the context of learning in primary schools, educational psychology has several important roles. First, educational psychology helps in the development of educational curriculum. In curriculum development, educational psychology considers students' affective, cognitive, and psychomotor aspects. Educational psychology also plays a role in shaping students' character through the implementation of culture and disciplinary rules in schools.